Pengaruh Etos Kerja, Motivasi Kerja, Gaya Kepemimpinan Demokratis Pada Efektivitas Kerja Badan Kepegawaian dan Pengembangan SDM di Kabupaten Bantul - Mukharomah, Finna Rahma (Gorontalo State University, 2025)
The purpose of this study is to ascertain how the Bantul Regency Personnel and Human Resources Development Agency's work effectiveness is impacted by work ethic, motivation, and democratic leadership style. Quantitative research is the methodology employed in this study. A questionnaire was used to gather study data, and the SPSS version 25 program and computer aid were used for analysis. There were 50 respondents in the Bantul Regency Personnel and Human Resources Development Agency's sample. Findings from this research indicate that while work motivation and democratic leadership style have no discernible impact on job performance, work ethic has a favorable and significant impact. Work effectiveness is positively and simultaneously impacted by work ethic, work motivation, and democratic leadership style.